General contractor business model for smart cities - Karam, Elie (Construction industry professional) (Information systems, web and pervasive computing series., 2022)
This book covers three principal subject areas: smart cities, general contractors and business models. The smart city concept is currently on the rise and cities around the world appear to be in a race to become smart, fast. Converting big cities into smart cities is a move that almost all cities around the globe have made, or will undoubtedly make in the near future, to be able to cope with the various repercussions of urbanization. Smartness is a vague term that could relate to anything and everything, such as infrastructure, people or governance. In this book, we focus our attention on smart buildings - large ones, in particular - and attempt to identify the key problems that France-based construction companies face today, in order to suggest plausible solutions. Our research findings show that no single business model can fit all smart cities worldwide. Using the general contractor business model for smart cities, this book proposes an original solution to managing smart city projects, bringing together architecture, construction and strategy.